The Design of an Automatic Soil Monitoring and Watering System for Ornamental Plants Using Microcontrollers Based on the Internet of Things (IoT) - Pratama, Wiko; Yuliansyah Siregar, Andree Rizky; Wahyudi, Muhammad (Bahasa Indonesia, 2023)
IoT-Based Ornamental Plant Watering System with YL-69 Sensor uses the Blynk platform as a user interface that allows users to monitor and control plant watering remotely. The YL-69 sensor is used to detect soil moisture levels, and the data obtained is sent to the cloud via IoT technology. Through the Blynk application, users can set watering schedules, monitor soil moisture in real-time, and receive notifications if humidity reaches a certain threshold. This system provides convenience, efficiency and seamless interaction between the user and the plants being cared for, improving water management and overall plant health.